Superlyophilic Interfaces and Their Applications. Issue 45 (12th October 2017) - Zhu, Zhongpeng; Zheng, Shuang; Peng, Shan; Zhao, Yong; Tian, Ye
Abstract: Superlyophilic interfaces denote interfaces displaying strong affinity to diverse liquids, including superhydrophilic, superoleophilic, and superamphiphilic interfaces. When coming in contact with these interfaces, water or oil droplets tend to spread completely with contact angles close to 0°, presenting versatile applications including self‐cleaning, antifogging, controllable liquid transport, liquid separation, and so forth. Inspired by nature, scientists have developed various kinds of artificial superlyophilic (SLPL) interfaces in the past decades. In terms of dimensional characteristics, the artificial SLPL interfaces can be divided into four categories: i) 0D particles, whose dispersibility or catalytic performance can be notably enhanced by superlyophilicity; ii) 1D micro‐/nanofibers or nanotubes/channels, which can efficiently transfer liquids with SLPL interfaces; iii) 2D flat SLPL interfaces, on which different functional molecules can be deposited uniformly, forming ultrathin and smooth films; and iv) 3D structures, which can be obtained by either constructing 0D, 1D, or 2D SLPL materials separately or directly fabricating random SLPL frameworks, and can always be used as functional coatings or bulk materials. Here, natural and artificial SLPL interfaces are briefly introduced, followed by a short discussion of the limit between lyophilicity and lyophobicity, and then a snapshot of methods to generate SLPL interfaces is given. Specific focus is placed on recent achievements of constructing SLPL interfaces from zero to three dimensions. Following that, broad applications of SLPL interfaces in commercial areas will be introduced. Finally, a short summary and outlook for future challenges in this field is presented. Abstract : Recent progress regarding superlyophilic interfaces with different dimensions is reviewed, including 0D particles, 1D fibers or tubes, 2D flat interfaces, and 3D materials. Moreover, the broad applications of superlyophilic interfaces are described, spanning from conductivity enhancement and self‐cleaning, liquid transport, and antifogging, to printing and liquid separation, heat transfer, and film fabrication.